New Horizons for Early Modern European Scholarship - Popper, Nicholas, 1977-; Blair, Ann, 1961- (Book collections on Project MUSE., 2021)
"This edited collection assembles a set of essays investigating the past, present, and future historiography of scholars who write about the cultural and intellectual history of early modern Europe. Contributors examine how scholars in recent decades have broken down traditional boundaries imposed on this period by exploring shifting conceptions of periodization, geography, genre, and evidence"--